Optimization of Polysaccharides Extraction from Spent Coffee Grounds (SCGs) by Pressurized Hot Water Extraction - Winatta Sakdasri; Kanyagorn Khamseng; Mookanda Wattanavaree; Yaowapa Chandeang; Ruengwit Sawangkeaw (My University, 2021)
Spent coffee grounds (SCGs) are a by-product of the food industry which contain a rich source of polysaccharides. This research was to study the extraction of polysaccharides from SCGs by environmentally friendly technic of pressurized hot water. The process optimization was investigated by response surface methodology (RSM) to produce the highest extraction yield with a different temperature of 80–120 °C, a pressure of 4–12 bars, and an extracted time of 60–180 min. The pressurized hot water showed an efficient technique to recover polysaccharides from SCG.
Keywords: Coffee grounds; Environmentally Friendly; Water extraction; Hot water extraction; Coffee research and impacts